Modeling dermatophytosis in reconstructed human epidermis: A new tool to study infection mechanisms and to test antifungal agents. (20th October 2016) - Faway, Émilie; Cambier, Ludivine; Mignon, Bernard; Poumay, Yves; Lambert de Rouvroit, Catherine
Abstract: Dermatophytosis is a superficial fungal infection of keratinized structures that exhibits an increasing prevalence in humans and is thus requesting novel prophylactic strategies and therapies. However, precise mechanisms used by dermatophytes to adhere at the surface of the human epidermis and invade its stratum corneum are still incompletely identified, as well as the responses provided by the underlying living keratinocytes during the infection. We hereby report development of an in vitro model of human dermatophytosis through infection of reconstructed human epidermis (RHE) by arthroconidia of the anthropophilic Trichophyton rubrum species or of the zoophilic Microsporum canis and Arthroderma benhamiae species. By modulating density of arthroconidia in the inoculum and duration of exposure to such pathogens, fungal infection limited to the stratum corneum was obtained, mimicking severe but typical in vivo situation. Fungal elements in infected RHE were monitored over time by histochemical analysis using periodic-acid Schiff-staining or quantified by qPCR-detection of fungal genes inside RHE lysates. This model brings improvements to available ones, dedicated to better understand how dermatophytes and epidermis interact, as well as to evaluate preventive and therapeutic agents. Indeed, miconazole topically added to RHE was demonstrated to inhibit fungal infection in this model.